Role of vaginal brachytherapy boost following adjuvant external beam radiotherapy in cervical cancer: Turkish Society for Radiation Oncology Gynecologic Group Study (TROD 04-002) - (:unkn) unknown (BMJ PUBLISHING GROUP, 2021)
Objective There are a limited number of studies supporting vaginal brachytherapy boost to external beam radiotherapy in the adjuvant treatment of cervical cancer. The aim of this study was to assess the impact of the addition of vaginal brachytherapy boost to adjuvant external beam radiotherapy on oncological outcomes and toxicity in patients with cervical cancer. Methods Patients treated with post-operative external beam radiotherapy +/- chemotherapy +/- vaginal brachytherapy between January 2001 and January 2019 were retrospectively evaluated. The treatment outcomes and prognostic factors were analyzed in patients treated with external beam radiotherapy with or without vaginal brachytherapy. Results A total of 480 patients were included in the analysis. The median age was 51 years (range 42-60). At least two intermediate risk factors were observed in 51% of patients, while 49% had at least one high-risk factor. The patients in the external beam radiotherapy + vaginal brachytherapy group had worse prognostic factors than the external beam radiotherapy alone group. With a median follow-up time of 56 months (range 33-90), the 5-year overall survival rate was 82%. There was no difference in 5-year overall survival (87% vs 79%, p=0.11), recurrence-free survival (74% vs 71%, p=0.49), local recurrence-free survival (78% vs 76%, p=0.16), and distant metastasis-free survival (85% vs 76%, p=0.09) rates between treatment groups. There was no benefit of addition of vaginal brachytherapy to external beam radiotherapy in patients with positive surgical margins. In multivariate analysis, stage (overall survival and local recurrence-free survival), tumor histology (recurrence-free survival, local recurrence-free survival and distant metastasis-free survival), parametrial invasion (recurrence-free survival and distant metastasis-free survival), lymphovascular space invasion (recurrence-free survival), and lymph node metastasis (distant metastasis-free survival) were found as negative prognostic factors. Conclusion Adding vaginal brachytherapy boost to external beam radiotherapy did not provide any benefit in local control or survival in patients with cervical cancer.
Keywords: radiotherapy; brachytherapy; uterine cervical neoplasms; RADICAL HYSTERECTOMY; ENDOMETRIAL CARCINOMA; CONSENSUS GUIDELINES; RANDOMIZED-TRIAL; STAGE; THERAPY; IRRADIATION; SURGERY; CHEMOTHERAPY; CRITERIA